2020
DOI: 10.3390/polym12010125
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Antibacterial Nanofibrous Membrane Infused with Essential Oil Extracted from Tea Tree for Packaging Applications

Abstract: Nanofibers made by electrospinning are being applied to an unlimited number of applications. In this paper, we propose the fabrication of antimicrobial functional nanofibers infused with essential oil for packaging applications that can extend the shelf-life of fruits. The morphology of nanofibers with different concentrations of essential oil was characterized by SEM and mechanical enhancement was confirmed via universal testing machine (UTM). The surface chemistry and crystalline of the nanofibers were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Electrospinning is an encapsulation method. There are many reports in relation to the encapsulation of essential oils by electrospinning (Ardekani et al, 2019;Lee et al, 2020;Rezaeinia et al, 2020;Teilaghi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrospinning is an encapsulation method. There are many reports in relation to the encapsulation of essential oils by electrospinning (Ardekani et al, 2019;Lee et al, 2020;Rezaeinia et al, 2020;Teilaghi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is an encapsulation method. There are many reports in relation to the encapsulation of essential oils by electrospinning (Ardekani et al., 2019; Lee et al., 2020; Rezaeinia et al., 2020; Teilaghi et al., 2020). Electrospinning is known for its low production costs, simplicity, flexibility, and ease of scaling up.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al fabricated tea tree essential oil (TTO)-loaded polyurethane (PU) nanofibers by electrospinning for packaging applications [ 160 ]. From the mechanical test results, it was observed that as the amount of TTO oil increased, the strength and strain values also improved.…”
Section: The Rationale Of Encapsulation Of Essential Oils Into Polymeric Nanofibersmentioning
confidence: 99%
“…Another food packaging application to extend the shelf life of fruits was carried out using PU/cinnamon oil by Lee et al [23]. Similarly, they used tea-tree-oil-infused PU nanofibers, characterized by mechanical, CO 2 reduction, and antibacterial tests, to extend the shelf-life of tomatoes [24]. Besides tea tree oil, PU nanofibers containing cinnamon bark and clove oils were also fabricated, and the antimicrobial activities were examined [25].…”
Section: Introductionmentioning
confidence: 99%